Breast cancer risk associated with atypical hyperplasia and lobular carcinoma in situ initially diagnosed on core‐needle biopsy. Issue 3 (10th October 2017) - Donaldson, Alana R.; McCarthy, Caitlin; Goraya, Shazia; Pederson, Holly J.; Sturgis, Charles D.; Grobmyer, Stephen R.; Calhoun, Benjamin C.
Abstract : BACKGROUND: Breast cancer risk estimates for atypical lesions are based primarily on case‐control studies of patients with open biopsies. The authors report the cumulative breast cancer incidence after a core biopsy diagnosis of atypical hyperplasia (ductal or lobular) or lobular carcinoma in situ. METHODS: A cohort study with central pathology review was conducted on 393 patients who had core biopsy diagnoses of atypical hyperplasia and lobular carcinoma in situ from 1995 through 2010. Follow‐up was available for 255 of 264 patients (97%) at a median of 87 months (range, 3‐236 months). RESULTS: There were 212 patients (54%) who were not upgraded on excision and had no personal history of breast cancer. Of these, 21 of 212 (9.9%) developed breast cancer, including 15 invasive carcinomas, 4 ductal carcinomas in situ, 1 pleomorphic lobular carcinoma in situ, and 1 unknown type. The prior core biopsy diagnoses were atypical ductal hyperplasia for 11 patients (52%) and atypical lobular hyperplasia/lobular carcinoma in situ in the remaining 10 patients (48%). The number of atypical foci in the core biopsy was not significantly associated with the subsequent development of breast cancer ( P  = .42). Of the 15 invasive carcinomas, 11 (73%) were ipsilateral, 11 (73%) were pathologic T1 tumors, 5 (33%) were pathologic N1 tumors, 13 (87%) were estrogen receptor‐positive, and 1 (7%) was amplified for human epidermal growth factor receptor 2. CONCLUSIONS: In patients who had an initial diagnosis of atypical hyperplasia or lobular carcinoma in situ on core biopsy, the 7‐year cumulative breast cancer incidence was 9.9%. Most tumors were ipsilateral, stage I, estrogen receptor‐positive, invasive carcinomas. The current data support close clinical and radiologic follow‐up for more than 5 years in this patient population. Cancer 2018;124:459‐65 . © 2017 American Cancer Society . Abstract : Long‐term follow‐up studies of patients diagnosed with atypical hyperplasia or lobular carcinoma in situ of the breast in open biopsies demonstrate a subsequent breast cancer incidence of approximately 1% to 2% per year. In this contemporary study of patients with atypical hyperplasia or lobular carcinoma in situ initially diagnosed on core biopsy, the cumulative breast cancer incidence appears to be similar.